Seletividade do clomazone em sementes de algodão tratadas com dietholate e acetato de zinco - Inoue, Miriam Hiroko; Cavalcante, Natan Ramos; Ben, Ronei [UNESP]; Mendes, Kassio Ferreira; Silva Possamai, Ana Cassia; Dallacort, Rivanildo (Univ Estadual Londrina, 2014)
The objective of this study objective was to evaluate the selectivity of pre-emergence applications the herbicide clomazone cotton seeds treated with dietholate and zinc acetate. The 4 x 2 factorial arrangement was adopted (4 seed treatment methods and 2 clomazone dosages), distributed in a randomized block design with 4 repetitions. In treatments where dietholate and zinc acetate were applied, rates of 0.4 kg ha(-1) and 8 ml per kg of seeds were used respectively. The clomazone rates used refer to 0.8 and 1.0 kg ha(-1). The cotton cultivar used was the Fiber Max 966 LL. Independent of treatment, all seeds were treated with tiametoxam insecticide and fludioxonil + metalaxyl-M fungicide at rates of 2.24 and 0.08 + 0.03 g per kg of seed, respectively, to control pests early and limit losses caused by pathogens in germination and seedling emergence. Dietholate and zinc acetate treatment had greater initial effect on cotton plants at 21, 30 and 45 days after application. In phytointoxication symptoms were observed for treatment with dietholate and zinc acetate during the evaluation periods. Seeds treated with dietholate, dietholate and zinc acetate or zinc acetate alone provided a higher number of bolls and seed cotton production compared to the control.
Clomazone selectivity in cotton seeds treated with dietholate and zinc acetate
Keywords: Phytointoxication; Gossypium hirsutum; Productivity